2020
DOI: 10.3389/fnagi.2020.586770
|View full text |Cite
|
Sign up to set email alerts
|

Regular Tai Chi Practice Is Associated With Improved Memory as Well as Structural and Functional Alterations of the Hippocampus in the Elderly

Abstract: Objective: The current study aimed at comparing the effects of Tai Chi (a motorcognitive exercise) with walking (an exercise without cognitive demands) on cognitive performance, brain structure, and brain function in the elderly. Methods: This cross-sectional study included 42 healthy elderly women within two groups: Tai Chi (n = 20; mean age = 62.90 ± 2.38 years) and brisk walking exercise (n = 22; mean age = 63.27 ± 3.58 years). All the participants underwent a cognitive assessment via the Montreal Cognitive… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 75 publications
0
46
0
1
Order By: Relevance
“…There were 13 randomized control trials with 17 articles [16][17][18]20,24,25,27,28,32,33,[40][41][42][43][44][45][46], 8 cross-sectional studies with 12 articles [21][22][23]26,[29][30][31]34,[36][37][38][39], and 3 single group pre-and postcomparisons with 3 articles [15,19,35]. Among these 24 studies, 17 of them with 21 articles had elderly subjects who were 60 years and older [20][21][22][23][24]26,[29][30][31][33][34][35][36][40][41][42][43][44][...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There were 13 randomized control trials with 17 articles [16][17][18]20,24,25,27,28,32,33,[40][41][42][43][44][45][46], 8 cross-sectional studies with 12 articles [21][22][23]26,[29][30][31]34,[36][37][38][39], and 3 single group pre-and postcomparisons with 3 articles [15,19,35]. Among these 24 studies, 17 of them with 21 articles had elderly subjects who were 60 years and older [20][21][22][23][24]26,[29][30][31][33][34][35][36][40][41][42][43][44][...…”
Section: Resultsmentioning
confidence: 99%
“…Among these 24 studies, 17 of them with 21 articles had elderly subjects who were 60 years and older [20][21][22][23][24]26,[29][30][31][33][34][35][36][40][41][42][43][44][45][46], 4/24 studies with 8 articles had mixed age groups with subjects 21-70 years old [17,19,27,28,32,[37][38][39], and 3 studies had healthy young subjects [16,18,25]. The majority of these studies used healthy subjects [15,16,18,[20][21][22][23][24][25][26][27][28][29][30][31][33][34][35][36]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous neuroimaging studies showed that TCC interventions can reshape the human brain structure and can lead to alterations of functional brain patterns, which, in turn, might foster the improvement of cognitive performance ( 34 ). For instance, in the study of Yue and colleagues ( 35 ), 42 healthy elderly women were assigned to two groups (TCC group and walking group) and underwent a cognitive assessment, as well as a functional magnetic resonance imaging to quantify between-group differences in brain structure and resting-state functional connectivity. In the above-mentioned study, it was noticed (i) that episodic memory in the TCC group was superior to that of the walking group, (ii) that the TCC group exhibited a higher gray matter density in the inferior and medial temporal regions and higher values of regional homogeneity in temporal regions as compared to the walking groups, and (iii) that neurobehavioural relationships exist (i.e., the correlation between gray matter density of the left hippocampus and episodic memory performance).…”
Section: Discussionmentioning
confidence: 99%
“…Very few studies have investigated the differential effects of exercise type on cognitive function in elderly populations ( Demurtas et al, 2020 ). A cross-sectional study was recently published ( Yue et al, 2020 ), indicating that as compared to older adults who engaged in brisk walking for at least 5 years (60 min × 5 times per week) Tai Chi practitioners demonstrated significantly better behavioral measure/cognitive function (delayed recall-memory function) and greater hippocampus. Researchers concluded that such superior effects may be attributed to complexity of Tai Chi movements (motor-coordinative training and movement sequence) and mindfulness-based training.…”
Section: Introductionmentioning
confidence: 99%